MARINE RESOURCE EXPLOITATION ETHICS: ENVIRONMENTAL PHILOSOPHY PERSPECTIVE IN FISHERIES MANAGEMENT - Mega Deza Tahta Rahmawati,; Nirmala Yusuf,; Fauzia Zees,; Amelya Mustamu,; Hasim, Hasim (Journal of Innovation Research and Knowledge, 2024)
The sea is a source of wealth and media in strengthening the unity of the Indonesian state. The large potential of marine resources, especially fisheries resources, makes a significant contribution to state income. Utilization of fisheries resources cannot be separated from various problems, especially regarding the exploitation process which does not pay attention to negative impacts on the environment. Excessive exploitation can also have a negative impact on marine waters as a whole, allowing conflicts to arise and even coming into conflict with international maritime law. To minimize the negative impacts of exploitation, conservation action is the right step and is in line with the concept of sustainable development goals (SDGs). From this article, it can be seen that the concepts of exploitation and conservation should be able to work in balance with the understanding and implementation of the concept of sustainable development. The process of exploiting fishery resources must also pay attention to its impacts, so that it does not cause harm to water conditions and without ignoring carrying capacity conditions existing environment and ecosystem